2016
DOI: 10.1515/cclm-2016-0151
|View full text |Cite
|
Sign up to set email alerts
|

Copeptin predicts 10-year all-cause mortality in community patients: a 10-year prospective cohort study

Abstract: Background: Copeptin, the C-terminal part of the arginine vasopressin (AVP) precursor peptide, is secreted in response to stress and correlates with adverse clinical outcomes in the acute-care hospital setting. There are no comprehensive data regarding its prognostic value in the community. We evaluated associations of copeptin levels with 10-year mortality in patients visiting their general practitioner (GP) for a respiratory infection included in a previous trial. Methods: This is a post hoc analysis includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…A similar 10-year post-hoc analysis of the prognostic biomarkers copeptin and MR-proANP, based on the same blood samples from the PARTI trial, has been published recently and showed that copeptin as well as MR-proANP were associated with 10-year all-cause mortality [52, 53]. …”
Section: Resultsmentioning
confidence: 96%
“…A similar 10-year post-hoc analysis of the prognostic biomarkers copeptin and MR-proANP, based on the same blood samples from the PARTI trial, has been published recently and showed that copeptin as well as MR-proANP were associated with 10-year all-cause mortality [52, 53]. …”
Section: Resultsmentioning
confidence: 96%
“…However, it turns out that it is also essentially a measure of all kinds of stresses and adverse events (714719), including those caused by infection (720729). …”
Section: Proteomic and Similar Biomarkers – Circulating And Placentalmentioning
confidence: 99%
“…A similar 10-year post-hoc analysis of the prognostic biomarker copeptin, based on the same blood samples from the PARTI trial, has been published recently and showed that copeptin was associated with 10-year all-cause mortality [43].…”
Section: Study Design and Settingmentioning
confidence: 60%
“…Nonetheless, according to our analysis MR-proANP is superior to copeptin, another osmo-dependent stress and inflammatory biomarker, in mortality prediction in the primary care setting [43] (see Supplemental Table 5). …”
Section: Discussionmentioning
confidence: 75%